Development and validation of the adolescent behavioural change Counselling Assessment Tool in Indonesia - Fransisca Handy Agung; Rini Sekartini; Nani Cahyani Sudarsono; Aryono Hendarto; Retno Asti Werdhani; Sri Retno Pudjiati; Lathifah Hanum; Affan Naufal; Susan M Sawyer (BMC, 2024)
Abstract Background Primary care provides an important context to engage adolescents and their families in healthy lifestyles with the goal of reducing future behaviour-related health problems. Developing a valid tool to assess health professionals' skills in behavioural change counselling is integral to improving the quality of clinical care provided to adolescents in Indonesia. Methods This work was nested within a project to develop a training program to enhance the behaviour-change counselling of adolescents and their parents by Indonesian primary care professionals. Initial item development was based on the content of the training module and the domain structure of the Behavioral Change Counselling Index (BECCI), a commonly used tool to assess counselling quality in healthcare settings. Expert panels were used to test content validity, while face validity was assessed by a group of trained psychologists. Inter-rater agreement was calculated prior to tests of construct validity and reliability, which involved psychologists rating 125 audio-taped counselling sessions between the health professional and adolescent patients, together with a parent. Results An initial 13-item tool was developed using a 1-5 Likert scale. Validity and reliability testing resulted in the decision to use a 14-item tool with a 0-3 Likert scale. The scale was found to have a Cronbach's α coefficient of 0.839 (internal consistency), and there was strong inter-rater agreement (0.931). Conclusion The assessment tool known as the Adolescent Behavioural Change Counselling Assessment Tool, is a valid and reliable instrument to measure Indonesian health professionals' behavioural-change counselling skills with adolescent patients. The tool provides an evaluation framework for future interventions that aim to improve health professionals' skills in addressing adolescent behaviour-related health problems.